The Interaction of Secondary School and University as a Condition for Self-Determination among High School Students - Berezhkovskaya E.L.; Kravtsov L.G. (Психолого-педагогические исследования)
The interaction of secondary school and university is most often focused not on the development of the personality of students, but on their choice of directions for further education. We assume that the level of development of the personality of adolescents does not correspond to the age-related task of professional self-determination. To test this hypothesis, we used a set of projective and survey methods aimed at studying the level of development of self-awareness, conceptual thinking and motivational sphere, including in relation to the choice of a profession. In addition, we studied the current interests of adolescents and their relationship to school. The study was conducted on a sample of 153 Moscow school students aged 14-17 years. The results obtained show that worries about the imminent graduation from school and the choice of a profession leaves an imprint on the state of schoolchildren, and success in this matter seems to them overvalued. The personal interests and plans of the children are suppressed by the fear of final exams and admission to a university. Based on the data obtained, we concluded that it is necessary to bridge the gap between the real interests and needs of schoolchildren and the educational environment. As a means for this, a special subdivision of the school and the university is proposed – "School Campus". The work of the "School Campus" can provide a change in the social situation of the development of schoolchildren, removing this contradiction.